Systematic long-term follow-up programs in patients with simple congenital heart diseases: how long is long? - Zuin, Marco; Rigatelli, Gianluca (Journal of Thoracic Disease, 2016)
Patients with simple congenital heart disease (CHD), such as patent ductus arteriosus (PDA), isolated atrial septal defects (ASDs) and ventricular septal defect (VSD), either with normal pulmonary vascular resistance or mild pulmonary stenosis, are not so rare in the general population (1).